Developing a Web-Based Interactive E-Learning Ecosystem for Arabic Vocabulary Mastery - Muhammad A'inul Haq; Kinnatul ‘Ashriyyah; Annisa Ainurrohmah; Ulya Mahfudhotun Najwa; Ahmad Wafiyyun Ni'am; Moh. Dhofir Ali Akbar; Muhammad Khabibullah (KURAS Institute, 2026)
Arabic vocabulary (mufradāt) learning often suffers from traditional, rote-memorization methods, resulting in low student motivation and passive classroom engagement. To address this, this study aims to design, develop, and evaluate a web-based, interactive e-learning ecosystem specifically for mufradāt instruction. The research employed a Research and Development (R&D) approach based on the ADDIE instructional design framework. A pre-experimental One-Group Pretest-Posttest design was conducted with 30 seventh-grade students at Islamic Junior High School ‘Madrasah Tsanawiyah’ (MTs) Assa’idiyah Manyar, Gresik. The developed platform integrated Google Sites and Wordwall to provide adaptive content, interactive game-based exercises, and real-time feedback. Data were collected through expert validation sheets, practicality questionnaires, and objective vocabulary tests, which were analyzed using quantitative descriptive statistics and N-Gain calculations. The findings revealed that the developed media is highly feasible, achieving validation scores of 80% for material and 90% for media design. Field trials demonstrated a High Practicality score of 88.33%, proving that the platform successfully stimulates student autonomy and minimizes latency. Furthermore, the intervention yielded a moderate but significant improvement in students' vocabulary mastery, evidenced by an N-Gain score of 0.45. In conclusion, the web-based interactive e-learning ecosystem is a valid, practical, and effective tool that significantly bridges pedagogical gaps in Arabic vocabulary learning. Integrating this technology-driven approach as a continuous pedagogical routine holds substantial potential for maximizing language acquisition.